2015
DOI: 10.1016/j.jbusres.2015.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Picking profitable investments: The success of equal weighting in simulated venture capitalist decision making

Abstract: Using computer simulation, we investigate the impact of different strategies on the financial performance of VCs. We compare simple heuristics such as equal weighting and fast and frugal trees with more complex machine learning and regression models and analyze the impact of three factors: VC learning, the statistical properties of the investment environment, and the amount of information available in a business plan. We demonstrate that the performance of decision strategies and the relative quality of decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…In another study in which the predictive accuracy of heuristics was benchmarked, Woike, Hoffrage, and Petty (2015) included another important aspect in their simulations, namely environmental properties. Instead of using real-world data sets, these authors artificially generated data sets and could hence control features such as the number of cues and the skewness of the cues' validities.…”
Section: Previous Research and Applicationsmentioning
confidence: 99%
“…In another study in which the predictive accuracy of heuristics was benchmarked, Woike, Hoffrage, and Petty (2015) included another important aspect in their simulations, namely environmental properties. Instead of using real-world data sets, these authors artificially generated data sets and could hence control features such as the number of cues and the skewness of the cues' validities.…”
Section: Previous Research and Applicationsmentioning
confidence: 99%
“…Financial indicators show an innovative company profile, which can certainly be considered as a potential supplier of the right shock absorber. Table 1.27 shows a summary of the transnational industrial group Freudenberg [53], which has officesin Russia and can be considered as a potential supplier of elastomeric dampers. Authoritative patents for devices of this class are also owned by Honda Motor and Porsche.…”
Section: Analysis Of Activity Of Leadersmentioning
confidence: 99%
“…Woike, Hoffrage, and Petty [53] compared simple heuristics with machine learning and regression models and showed that simple heuristics is competitive with more complex VCs decision strategies. However, is it possible to synthesize analytic and heuristic approaches?…”
Section: Using Heuristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, for venture capital decisions, Woike, Hoffrage, and Petty (2015) found that the decision quality when using equally weighted binary cues is comparable to more complex strategies, but even more robust. Graefe (2015) argued that estimating coefficients (weights) of predictors in multivariate models is only reasonable for large and reliable datasets and few predictors.…”
Section: Introductionmentioning
confidence: 99%